The role of trauma and positive youth development in polysubstance use among rural middle school students: a latent class analysis - Andrew P. Zervos; Devon J. Hensel; Rebecca James; Abby Hunt; Mary A. Ott (BMC Public Health, 2022)
Abstract Background Rural youth often begin developing polysubstance use and other risk behaviors during middle school. However, little polysubstance use research focuses on rural middle school youth. Our research uses Latent Class Analysis to understand existing patterns of rural middle school polysubstance use and risk and protective factors associated with polysubstance use. Methods We used survey data from a rural middle school pregnancy prevention program (N = 2,708). The survey included measures of demographics, lifetime substance use, trauma (adverse childhood experiences and bullying victimization) and aspects of youth development (parent communication on drugs and alcohol, parent connectedness and school connectedness). We used latent class analysis to produce participant polysubstance use profiles and multinomial regression to examine associations between polysubstance use, demographics, trauma and aspects of youth development. Results We categorized our participants into four latent classes. Our analysis classified 2.2% of participants as Regular Polysubstance users, 6.9% as Polysubstance experimenters, 19% as Vape + Alcohol experimenters and 71.9% as Non-Users. More adverse childhood experiences were associated with greater risk of polysubstance use and experimentation. Bullying was positively associated with greater risk of vape and alcohol experimentation. Higher reported parental and school connectedness were associated with lower risk of high frequency polysubstance use. Higher reported school connection was also associated with lower risk of polysubstance experimentation. Conclusion Rural substance use prevention programs should begin during middle school, as polysubstance use development is common among rural middle schoolers. These programs should be trauma informed and focus on connectedness as a modifiable factor to reduce risk of polysubstance use development. Trial registration This article does not report results of a health care intervention on human participants.